Discursos ocultos de "la guerra de los conventillos" en Pasto (1835-1840): Historia, memoria y contrahegemonía (2023)
The independence processes, which occurred in Colombia during the nineteenth century, are analyzed by the historicist notion as part of the prevailing discourses monopolized by colonialist and used to determine certain social classes in our territory. However, the variety of discourses presented during the period of independence in the various regions of what is presently Colombia's territory, rests not on homogeneity but on the heterogeneity submitted to power. It is impossible to investigate the historical narratives through the speeches that were not part of the public stage during the War of the Supremes or Tenement. These speeches regarding the hegemonic discourses became invisible and only some of them survived through the collective memory in alternate scenarios (such as, the hidden transcript) in Pasto.